Association between polymorphisms of ABCB1 and prognosis in esophageal squamous cell carcinoma patients treated with taxane. (16th June 2022) - Sun, Zhiwei; Yang, Xin; Du, Feng; Shi, Youwu; Sun, Jing; Jia, Jun; Liu, Chuanling; Xiao, Yanjie; Yu, Jing; Zhang, Xiaodong; Yang, Ying
Abstract: Background: In China, most esophageal cancer patients are squamous cell carcinomas and are treated with taxane‐containing regimens; however, few studies have examined taxane pharmacokinetics genes and esophageal squamous cell carcinoma (ESCC) prognosis. Methods: In total, 227 pathologically confirmed ESCC patients receiving chemotherapy with taxane were included in the analysis. We genotyped seven SNPs (rs1045642, rs2032582 and rs3213619 of ABCB1; rs2231137 and rs2231142 of ABCG2; and ABCC1 rs246221 and ABCC2 rs3740066) and analyzed their relationship with overall survival. Results: With a retrospective cohort study design, by Cox regression and semi‐Bayesian shrinkage, in the genetic recessive model, the variant homozygote of ABCB1 rs1045642 was inversely associated with survival (semi‐Bayesian shrinkage crude hazard ratio = 1.82, 95% confidence interval = 1.00, 3.31; p  = 0.0482). Conclusions: Because of inherent defects of the research itself, the finding that the ABCB1 rs1045642 variant was related to poor prognosis in ESCC patients treated with taxane‐containing regimens needs to be tested in a larger population and by using more genetic and molecular mechanism experiments. Abstract : Compared to the wild homozygote GG (image A) and the heterozygote GA (image B) genotypes, the variant homozygote AA (image C) of ABCB1 rs1045642 was related to a worse prognosis.